Demand for global health training and experiences among emergency medicine trainees in Australia and New Zealand. (17th February 2020) - Mitchell, Rob D; Mitchell, Rebecca L; Phillips, Georgina A; Jayaratnam, Skandarupan; Jamieson, Jennifer; O'Reilly, Gerard M
Abstract: Objective: Demand for global health (GH) training and experiences among emergency medicine trainees is unknown. The primary objective of the Trainee Interest in Global Health Training (TIGHT) study was to quantify the number of trainees interested in completing a rotation in a resource‐limited environment within a low‐ or middle‐income country during their specialty training. Methods: A cross‐sectional study of trainees in seven specialty training programmes was conducted between August and October 2018. Data were collected using a voluntary, anonymous, self‐reporting, web‐based survey. This study describes the results of a planned sub‐group analysis of ACEM trainees. Results: There were 203 respondents among 2525 ACEM trainees. Although only a small number (36/198, 18.2%) had undertaken a GH experience as a specialty trainee, 85.6% (167/195) were keen to do so. The vast majority of respondents (179/194, 87.1%) were interested or very interested in having their GH experience accredited for training, but 68.9% (133/193) reported that accessing a suitable placement was a barrier. More than 79% (147/186) expressed interest in undertaking an integrated GH training or fellowship programme as an adjunct to specialty training. Conclusions: Notwithstanding the limitations of a self‐reporting survey with a sub‐optimal response rate, there is significant demand for GH training and experiences among ACEM trainees. These findings should inform the development of safe and effective global emergency care training pathways, underpinned by mutually beneficial, international partnerships with educational and development objectives.